Pelaksanaan Inovasi Guru dalam Pembelajaran Pendidikan Agama Islam di SDN 20 Baraka - Mustiha, Mustiha (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Implementation of Teacher Innovation in Islamic Religious Education Learning for Students at SDN 20 Baraka. The purpose of this study was to find out the innovations made by teachers in Islamic religious education learning at SDN 20 Baraka, to find out the factors that support and hinder the implementation teacher innovation in Islamic religious education learning at SDN 20 Baraka, to find out the results of implementing Islamic religious education learning innovations at SDN 20 Baraka. The type of research used is a qualitative approach where researchers work directly in the field to collect data through observation, interviews and documentation, then collect data using data reduction methods, data presentation and verification. Researchers used a research sample by selecting several people consisting of the chairman of the foundation, school principals, teaching staff and students. The data received was then analyzed to find out how big the implementation of teacher innovation was in learning Islamic religious education at SDN 20 Baraka. The results of research on the implementation of teacher innovation in learning Islamic religious education at SDN 20 Baraka are considered quite successful. This can be seen from the field results which show students have an average value above the Minimum Completeness Criteria (KKM). This success is supported by several supporting factors, both internal and external factors that increase learning innovation in students. This was also confirmed from the results of interviews conducted by researchers where students were very enthusiastic in receiving lessons.